AS739, AT693, AU197 and AU734 antibodies label the spike S protein from SARS-CoV-2 by western blot - Lazzarotto, Célia; Berkcan, Serkan; Volery, Maxime; Gozlugol, Ezgi; Gosetto, Margaux; Oppliger, Ezia; Gil, Daniel; Poncet, Clément; Sassi, Ali; El Matribi, Zacharie; Jaques, Emma; Chammartin, Nylsa; et al. (Antibody Reports, 2021)
The recombinant antibodies AS739, AT693, AU197 and AU734 detect by western blot the spike S protein from SARS-CoV-2.